Migration and Use of Remittance in Urban Hill Settings of Ramechhap (Voice of Teacher, 2024)
This article-based follow Nepalese people’s lives and households got better because of money sent home by migrants. A significant change has occurred in the country due to outmigration, remittances, and development. In Nepal, migration and remittances are what keep people in rural areas safe. The article found minimal micro-level data on the allocation of remittance inflows relative to national benchmark sand and next that the remittance receipt was below the national average, using the National Living Standard Survey of Nepal as a reference, Focused on NELM, international, and social network theory. Which survey and sample size. The cross-sectional study comprised 260 residents from Ramechhap and Manthali, all of whom faced similar distractions. In finding this article, the higher percentage of households, 97.7 %, received remittances than only 83.1 per cent in Mantali (83.1 (χ² = 15.97, p = 0.001). There were no significant correlations between remittance volume and family structure, ethnicity, pre-migration occupation, or migration motivations (p>0.05). Most people spend less than the national average monthly expenditure of NPR 32,338.53, a paradox given high remittance inflows and low spending. Many families spend almost half their budget on food and other necessities, priorities education and health, yet still do not meet the minimum standards. Migration and remittances help people in a rural economy structurally constrained to cope and adapt, but only if there are more institutions and policies to support them. It cannot lead to widespread economic growth in Nepal.